OS 36-05 TETRAHYDROBIOPTERIN REVERSE LEFT VENTRICULAR HYPERTROPHY AND DIASTOLIC DYSFUNCTION THROUGH THE PI3K/p-Akt PATHWAY IN SPONTANEOUSLY HYPERTENSIVE RATS. (September 2016) - Wang, Qiongying; Chang, Peng; Xu, Han; Bai, Feng; Yu, Jing
Abstract : Objective: Hypertension induced hypertrophy and diastolic dysfunction and is associated with cardiac oxidation and reduced NO production. We hypothesized that tetrahydrobiopterin (BH4) can regulate the phosphatidylinositol 3-kinase/protein kinase B (PI3K/Akt) signaling pathway and reverse cardiac hypertrophy and diastolic dysfunction in spontaneously hypertensive rats. Design and Method: Ten-week-old male spontaneously hypertensive rats (SHR) and age-matched normotensive control Wistar-Kyoto (WKY) rats were divided into five groups, WKY, WKY + BH4, SHR, SHR + BH4 and SHR + VAL. Diastolic function were assessed by echocardiography and hemodynamics. The expression and phosphorylation level of PI3Kand Akt were assayed with western blot analysis. High performance liquid chromatography (HPLC) analysis was used to measure BH4 and biopterins. Quantitative real-time- Polymerase Chain Reaction (PCR) and immunohistochemistry were used to test cardiac hypertrophic genes and expression of Bax and Bcl-2 in the myocardium. Results: In SHR diastolic dysfunction was accompanied by concentric hypertrophy, cardiac oxidation, a reduction in cardiac BH4 and NO production. Administered with BH4 and Valsartan for four weeks, the data showed that both can reverse hypertrophy and improve diastolic function.BH4 and Valsartan blunted the expression of hypertrophy markers α-skeletal actin (α-SA) and β-myosin heavy chain (β-MHC), only BH4 reduced hypertension induced myocardial fibrosis and expression of transforming growth factor-β1(TGF-β1). BH4 reduced cardiac oxidant stress and increased NO production. Exogenous BH4 increased the phosphorylated Akt level and enhanced expression of Bcl-2. Conclusions: Less BH4 and reduced NO increases myocardial hypertrophy and cardiac oxidative stress, which exacerbates diastolic dysfunction. Exogenous BH4 ameliorates cardiac hypertrophy and diastolic dysfunction through the PI3K/p-Akt pathway. BH4 may be a potent therapy for hypertension with diastolic dysfunction.